PRAKTIK PENANDAAN DALAM IKLAN - Murtono, Taufik (Seni Media Rekam ISI Surakarta, 2010)
Visual signing at advertisement is a meaning attaching effort, considering almost all of the advertised products did not have specific value. A number of products can be replaced by other brand within same category. Usually, in marketing communications world, this kind of product has a lot of competitors. Having no differentiation causing the product has no meaning in the consumers’ mind. The situation leads the product to get a sign from outside of itself.Keywords: advertisement, sign, meaning, practice